Evaluation the Efficiency of Various Types of Corrosion Inhibitors Used for Basrah Water Storage Tanks - Jasim, Haider Hadi; Al-Hussain, Read Abd; Sadeq, Ahmed Shawqi (Al-Nahrain Journal for Engineering Sciences, 2020)
In this paper, the efficiency of six different types of corrosion inhibitors used in Basrah drinking water tanks was assessed using a potentiostatic test method. The mechanism of adsorption of silicate and phosphate inhibitors in AISI 316 stainless steel surfaces and the effects of different water components in inhibitors are discussed in detail. The values of corrosion rate obtained from the Potentiostatic test showed that the protection against corrosion in the presence of inhibitors is better compared to the case of absence of inhibitors. The results of the six types of corrosion inhibitors tested showed that the inhibitory efficacy is higher below the temperatures 45oC, but when raise the temperature above 45oC the inhibitory efficiency becomes to decrease. Also, the test results indicated that the corrosion inhibitor involves silicate products provided more inhibited efficiency compared to the phosphate inhibitor alone or used the combined silicate/phosphate corrosion inhibitor. The inspection of the surface of the tested samples using optical methods shows that the pitting corrosion is demonstrated on the specimen surfaces after testing with or without inhibitors.